A comparative DFT study of electronic and optical properties of Pb/ Cd-doped LaVO4 and Pb/Cd-LuVO4 for electronic device applications - Jameel, Muhammad Hasnain; Agam, Mohd Arif; Roslan, Muhammad Sufi; Hasan Jabbar, Abdullah; Malik, Rami Qays; Islam, Muhammad Usama; Raza, Ali; Subhani, Rasheed Ahmad (Elsevier, 2023)
A First-principles study based on density functional theory was accomplished to examine the different properties of ABVO4 (A = Pb/Cd, B––La/Lu) materials such as structural, optical, and electronic properties. The band gap of Pb/Cd-doped LuVO4 is found to be remarkably and significantly decreased from 2.921 to 1.71eV as compared to a decrement of 3.455 to 2.650eV in Pb/Cd-doped LaVO4. Under the DFT study, Pb (Lead) and Cd (Cadmium) are appropriate materials for band gap decrement of LuVO4 and LaVO4. The nature of the band gap was found indirect moreover band gap indicated that materials are prominent semiconductors. Pb/Cd is doped at the vanadium (V) sites, which are more advantageous than the La/Lu sites. By capturing Pb/Cd at the V sites in LuVO4/ LaVO4, additional gamma points were incorporated into the electronic band gap energy (Eg). A significant decrement is found in the band gap as well as optical conductivity. After the substitution of different impurities of Pb/Cd the energy absorption peaks are increased. It is also examined that after doping of Pb/Cd optical conductivity shifted toward larger energy because of the band gap. Both Pb/Cd-doped LuVO4 and Pb/Cd-doped LaVO4 compounds have high optical conductivity, refractive index, and energy absorption moreover Pb/Cddoped LuVO4 is a more appropriate material as compared to Pb/Cd-doped LaVO4 for electronic device applications.